Crafting history archiving and the quest for architectural legacy - Yaneva, Albena (Expertise, 2020)
What constitutes an archive in architecture? What forms does it take? What epistemology does it perform? What kind of craft is archiving? Crafting History provides answers and offers insights on the ontological granularity of the archive, and its relationship with architecture as a complex enterprise that starts and ends much beyond the act of building, or the life of a creator.We learn how objects are processed and catalogued, how a classification scheme is produced, how models and drawings are preserved, how born-digital material battles time and technology obsolescence. We capture archiving in its mundane, and practical course. We follow the work of conservators, librarians, cataloguers, digital archivists, museum technicians, curators, and architects.Based on ethnographic observation of the Canadian Centre for Architecture and interviews with a range of practitioners, including Álvaro Siza and Peter Eisenman, Yaneva traces archiving through the daily work and care of all its participants, scrutinizing their variable ontology, scale, and politics. Yaneva addresses the strategies employed by practicing architects to envisage an archive-based future, and tells a story about how architectural collections are crafted so as to form the epistemological basis of Architectural History